On Comonotony Approximation in Quasi Normed Space - Nada Zuhair Abd AL-Sada (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we are introduce the relationship between  the best approximation by the polynomial  and modules of smoothness , and the modules of smoothness  , in quasi normed  space ,and the polynomial  which change its comonotone approximation with the function  at every point in an interval .